Phishing Cyber Security Threats - Trisolvena, Muhammad Nana; Saputra, Nana Handre (Ann Publisher, 2024)
Phishing is a growing threat in the realm of cybersecurity, where cybercriminals use various phishing techniques to steal sensitive information from individuals and organizations. In practice, phishing aims to obtain personal, account, and financial data by impersonating trusted parties through fake emails, websites, text messages, or social media. The term